Pengaruh Sistem Informasi Keuangan dan Manajemen Terhadap Peningkatan Tunjangan Kinerja Pegawai Non PNS di Puskesmas Kecamatan Kramat Jati - Herni Pujiati; Amelia Sendi (Universitas Mohammad Husni Thamrin, 2020)
Every organization has to improve their performance. This condition encourage companies to use information system to carry out its daily task. The implementation of information system in an organization will accelerate and simplify the completion of the task by every employee. This condition is expected to improve the performance of employees in the company.The purpose of this research is to examine the influence of Financial Information System and Management to the improvement of performance allowance of non PNS employees at sub-district health center of Kramat Jati. This research is a quantitative research. The data analysis technique has been done by using simple refression analysis. It can be concluded from the result of the research that the implementation of accounting information system has significant and positive influence to the performance of the employees has been applied in the company properly, the performance of the employees in the company will be improved as well. The implementation of accounting information system is strongly influenced by the human resources who are owned by the company. The company should always conduct the competency of the human resource about information and technology. Competency and knowledge of the human resources is needed by the company in maximizing the use information technology.Keywords: Performance allowances, financial information systems, simple linear regression.